Using Serious Games to Facilitate Collaborative Water Management Planning Under Climate Extremes. (2nd September 2019) - Bathke, Deborah J.; Haigh, Tonya; Bernadt, Tonya; Wall, Nicole; Hill, Harvey; Carson, Andrea
Abstract: Sustainable management is a complex process that involves balancing the competing interests of the human, plant, and animal communities that depend on watershed resources. It involves developing and implementing plans, programs, and projects that sustain and enhance watershed functions while taking into account the natural, social, political, economic, and institutional factors operating within the watershed and other relevant regions. Examples of such factors include crosscutting mandates by different levels of government, conflicting objectives across sectors, and the constraints and uncertainty of the availability and accessibility of the resources within the watershed. One way to address these complexities is with public participation processes designed to share knowledge among disciplinary experts, policy‐makers, and local stakeholders and provide outcomes, which inform the creation of sustainable watershed management plans. Serious games (i.e., games played for purposes other than pure entertainment) are an example of such processes. Here, we present a case study of how a serious game, called the multi‐hazard tournament, was used to facilitate watershed management by promoting social learning, cross‐sectoral dialogue, and stakeholder participation in the planning process.